APLIKASI JENIS MIKORIZA TERHADAP PH DAN P-TERSEDIA PADA ULTISOL YANG DI TANAMI KACANG TANAH (ARACHIS HYPOGAEA L.) - Ibnu Yasier; Syakur Syakur; Helmi Helmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Low pH and P-available in Ultisol be a factor for plant. The research was aimed to know the effect of applicating types of mycorrhizal of pH and P-available in Ultisol. The research used randomized complete block design non-factorial, which consists of control (M0), Glomus sp (M1), Gigaspora gigantea (M2), and Acaulospora tuberculata (M3). The parameters were pH and P-available. The result of the research showed that the application of Gigaspora gigantea affected other parameters pH while the mycorrhizal type application Acaulospora tuberculata affected other parameters P-available. The application of Glomus sp was significantly affected to all parameters. While, control and the application of Acaulospora tuberculata was not significant effect to all parameters.Keywords : Kinds of Mycorrhizal, pH, P-available, Ultisol